Transtornos do sono-vigília em mulheres com câncer de mama e fadiga secundária a quimioterapia - Oliveira, Taliana da Silva Gomes (2018)
Introduction: Sleep wake disorders have been a frequent complaint in women with breast cancer in chemotherapy. Objective: to evaluate sleep wake disorders in women with breast cancer, who presented fatigue secondary to chemotherapy (FSQ). Theoretical-methodological course: This is a prospective study, with mixed methods approach. The sample consisted of 47 women, presenting FSQ, identified in nursing consultation, through the nursing diagnosis and the Fatigue Pictogram. Of the 47, 15 women were identified as key participants and interviewed for the qualitative approach. Validated instruments were: Piper Fatigue Scale Revisited (PIPER) and Pittsburgh Sleep Quality Index (PSQI-BR); for a qualitative approach, we used semi-structured audio-video interviews. Data collection occurred at the time of diagnosis of fatigue (T1), and in the next chemotherapy cycle (T2). For statistical analysis, the t-Test compared the quantitative variables of the instruments, in T1 and T2. The association between variables, sleep quality and fatigue was measured by Spearman's non-parametric correlation. The level of significance was set at p <0.05. To analyze the qualitative data, the Bardin content analysis was performed. Results: The Fatigue Pictogram showed that 61.68% of the participants reported moderate to severe fatigue; 57.44% had an important impact in the execution of daily assignments. Although from T1 to T2 poor sleep quality remained, there was a decrease in the means of the overall PSQI-BR score from 9.34 to 8.89. This difference was not statistically significant (p = 0.377) to reflect improvement in sleep quality. The correlation between fatigue and sleep quality was only significant in T1 (p = 0.001), showing that the higher the intensity of fatigue, the greater the sleep wake disorder. Women's perceptions regarding CSF and sleep quality were described in six categories: Fatigue perceptions; Factors that contributed to aggravate fatigue; Strategies for managing fatigue; Sleep quality before and during chemotherapy; Non-pharmacological strategies for sleep induction and Factors that hinder sleep. The participants understood that sleep wake disorders and fatigue were from the chemotherapy treatment and presented different perceptions about the quality of their sleep. They also referred to emotional and psychological aspects related to FSQ, which caused losses to sleep and were responsible for the worsening of fatigue. Final Thoughts: Poor sleep quality and FSQ are symptoms presented by most women with breast cancer; when associated may manifest more intensely. It is up to the multiprofessional health team to recognize these symptoms early, so that the interventions are effective, and corroborate to improve the quality of life of these women.